Subtraction CTA: An Alternative Imaging Option for the Follow-Up of Flow-Diverter-Treated Aneurysms? - Duarte Conde, M.P.; de Korte, A.M.; Meijer, F.J.A.; Aquarius, R.; Boogaarts, H.D.; Bartels, R.H.M.A.; de Vries, J. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: This was a pilot study to explore the diagnostic accuracy and safety of subtraction CTA combined with a single-energy metal artifact reduction algorithm (SEMAR) compared to DSA for the evaluation of intracranial aneurysm occlusion after flow diverter treatment.MATERIALS AND METHODS: We included patients treated with a flow diverter for an unruptured intracranial aneurysm between November 2015 and November 2016. The patient cohort comprised 2 groups: those who underwent follow-up imaging 1 month after flow-diverter treatment and those with a known residual intracranial aneurysm after flow diverter treatment who underwent imaging at regular follow-ups. Full-brain subtraction CTA was performed on a 320–detector row CT system. A low-dose non-enhanced volume acquisition was followed by a contrast-enhanced volume CTA. Iterative and noise-reduction filters, SEMAR, and SURESubtraction algorithms were applied. DSA was performed on a flat panel C-arm angiography system. Standard posteroanterior, lateral, 3D, and detailed 2D acquisitions were performed. Imaging was independently scored by 2 clinicians. Aneurysm occlusion (Raymond scale) was our primary outcome parameter.RESULTS: Thirteen intracranial aneurysms were evaluated with subtraction CTA and DSA. Nine aneurysm remnants were demonstrated by both subtraction CTA and DSA. The sensitivity and specificity of subtraction CTA for the detection of aneurysm occlusion were 100% (95% CI, 82.41%–100%) and 100% (95% CI, 67.55%–100%), respectively. Agreement between readers was perfect (κ = 1.0). The smallest neck remnant detected on subtraction CTA was 1.2 mm. No complications occurred.CONCLUSIONS: Subtraction CTA with single-electron metal artifact reduction is effective in the reduction of metal artifacts of flow diverters and might therefore be a viable alternative in the assessment of intracranial aneurysm occlusion after flow diverter treatment.IAintracranial aneurysmFDflow divertersCTAsubtraction CTASEMARsingle-electron metal artifact reduction